Analisis Dampak Variasi Konstan Pengontrol PID Pada Kontrol Kecepatan Motor DC - Amanda, Nova; Franky, Franky; Dwisaputra, Indra; Andik Setiawan, I Made (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The implementation of a PID (Proportional-Integral-Derivative) controller for speed regulation of a DC motor, employing both the Ziegler-Nichols method and a Iterative Methods approach for PID parameter tuning. DC motors are integral to various applications, requiring precise speed control for optimal performance. The Ziegler-Nichols method was utilized to initially estimate the PID parameters (Kp, Ki, and Kd), using system response data to derive values from both the L and T parameters as well as the Ku and Tu parameters. The experimental setup involved a DC motor controlled via PWM (Pulse Width Modulation), with speed measurements taken from a tachometer for validation. Results demonstrated an average percentage error of 2.08% between serial monitor readings and tachometer measurements, indicating high accuracy. Further refinement using the Iterative Methods identified optimal PID settings (Kp = 0.095, Ki = 0.08, Kd = 0.02) that provided stable and precise speed control. This study confirms the Ziegler-Nichols method as a reliable foundation for PID tuning, while also highlighting the effectiveness of iterative adjustments for achieving fine-tuned control. Future work may explore adaptive control strategies to enhance the system's responsiveness to changing conditions.